2019
DOI: 10.1111/1750-3841.14840
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Antihyperglycemic Compounds from Vigna angularis Extracts

Abstract: Functional foods that inhibit α‐amylase and α‐glucosidase activity are effective for regulating the blood glucose level and preventing hyperglycemia. Extracts of adzuki beans (ABs, Vigna angularis), widely eaten in East Asia, can inhibit α‐amylase and α‐glucosidase activity. In this study, we identified and evaluated the components in an AB water extract (ABWE) after boiling, which is an essential process for cooking ABs. The ABWE before boiling inhibited α‐amylase and α‐glucosidase activity and the boiled ABW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…1 presented the highest catechin and rutin contents; a previous study suggested that catechin in dietary beans presented an inhibitory response toward fungal amylase ( 58 ). Furthermore, catechin showed inhibitory activities to α-amylase, lipase, and α-glucosidase, which is directly linked with blood sugar content ( 10 , 59 , 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…1 presented the highest catechin and rutin contents; a previous study suggested that catechin in dietary beans presented an inhibitory response toward fungal amylase ( 58 ). Furthermore, catechin showed inhibitory activities to α-amylase, lipase, and α-glucosidase, which is directly linked with blood sugar content ( 10 , 59 , 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…3 (21)]. Kuriya et al [129] revealed that flavonoids, namely, catechin 7-O-β-D-glucopyranoside [ Fig. 3 (11)], epicatechin 7-O-β-Dglucopyranoside [ Fig.…”
Section: Antidiabetic Activitymentioning
confidence: 99%
“…This is due to the fact that plant‐based diets offer cost‐effective and relatively safe alternatives, often associated with fewer severe gastrointestinal complications (Yilmazer‐Musa et al ., 2012; Xu et al ., 2019). Previous studies have demonstrated the potential of extracts from apple (Raphaelli et al ., 2019), seaweed (Zaharudin et al ., 2019) and Adzuki beans (Kuriya et al ., 2019) in modulating postprandial blood glucose via α‐glucosidase inhibition. Thus, plant‐derived bioactive compounds have potential as α‐glucosidase inhibitors, offering a strategy for postprandial hyperglycaemia management.…”
Section: Introductionmentioning
confidence: 99%